The differences in postural reactions between scoliosis and scoliotic posture - Jacek Wilczyński; M Kabała; Michał Jerzy Paprocki; Paweł Rychter; D Dworakowska (Kazimierz Wielki University, 2017)
The aim of the research was to demonstrate the differences in amplitudes of postural reactions in girls with scoliotic posture and idiopathic scoliosis. 28 girls aged 7-18 years old were involved in the study. Children attended to the Interschool Centre of Corrective Exercises in Starachowice. The research was conducted in June 2011. Spine research was made by Exhibeon digital radiography. Based on the size of the angle of spinal curvature there were identified: scoliotic posture: 1-9° and scoliosis: ≥10°. Postural reactions were examined by static-dynamic Tecnobody's ST 310 Plus Stability System platform. There were 21 (75%) children with scoliotic posture, and 7 (25%) with idiopathic scoliosis. Student's t-test showed a significantly higher postural reactions for scoliosis in relation to scoliotic postures in case of: Average Forward-Backward Speed (OE), (p=0,05), Medium-Lateral Standard Deviation X (CE), (p=0,002), and Ellipse area (CE), (p=0,012). To verify the significant differences, demonstrating the lack of homogeneity of variance, the Mann-Whitney U-test has been used, which showed a significant differences between the scoliotic posture and scoliosis in case of: Medium-Lateral Standard Deviation X (CE), (p=0,0012), Average Forward-Backward Speed (OE), (p=0,0548), and Ellipse area (CE) (p=0,0047). Together with an increase of the angle of curvature, the value of these postural reactions also grew. Most of postural reactions didn't fit the norm.